2001
DOI: 10.1093/jjco/hye115
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Health-related Quality of Life During and After High Dose Rate Brachytherapy Followed by External Beam Radiotherapy for Prostate Cancer

Abstract: Background:The optimal protocol for combining high dose rate brachytherapy and external beam irradiation as treatment for localized prostate cancer is unknown. Toxicity rates and clinical and biochemical outcomes should be evaluated to validate the current treatment protocol. Methods: Fifty-eight patients were treated for prostate cancer with high dose rate brachytherapy followed by 30 Gy of external beam radiation therapy. Toxicity during treatment and for 12-18 months thereafter, and treatment-related morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
(23 reference statements)
1
17
0
1
Order By: Relevance
“…Most outcome measures, however, showed a recovery to baseline levels 12 months after radiation therapy. 20 Finally, a Swedish study on HRQOL after external beam radiotherapy and brachytherapy revealed that the negative contribution from neoadjuvant androgen deprivation therapy on symptom development seemed to be substantial but mostly transitory. 21 Our study also showed a decrease in HRQOL after treatment followed by an increase between 6 weeks and 3 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most outcome measures, however, showed a recovery to baseline levels 12 months after radiation therapy. 20 Finally, a Swedish study on HRQOL after external beam radiotherapy and brachytherapy revealed that the negative contribution from neoadjuvant androgen deprivation therapy on symptom development seemed to be substantial but mostly transitory. 21 Our study also showed a decrease in HRQOL after treatment followed by an increase between 6 weeks and 3 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional functioning 82 (20) 88 (15) 84 (21) 85 (18) 85 (21) 86 ( 89 (15) 90 (14) 85 (21) 90 (15) 84 (21) Ͻ0.050 Ͻ0.050…”
Section: Ns Nsunclassified
“…A Japanese group assessed HRQOL prospectively with the SF-36 questionnaire and self-formulated prostate-specific questions during the first 18 months after treatment with five times 4 to 5 Gy of HDR brachytherapy followed by ten 3-Gy fractions Table III of EBRT to the prostate and seminal vesicles [9]. While significant deterioration was seen in five domains of SF-36 at one month after radiotherapy, these values returned to normal by 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The results are summarized in Table V. In addition, centres have reported their experience using the Syed free-style template technique [25,26]. There has been increasing experience with the use of HDR brachytherapy as a boost to external beam radiotherapy, and this has been evidenced in reports from a number of institutions of 5 years bNED survival in the range of 67 Á93%.…”
Section: Clinical Outcomementioning
confidence: 99%
“…There is growing knowledge that self-assessed questionnaires are more sensitive when describing the presence of side effects compared to different methods where physician report the side effects [26,33,34]. However, the RTOG scores for acute and late radiation reactions have reached a consensus and a widespread use, which makes it practical when comparing different radiotherapy methods.…”
Section: Side Effectsmentioning
confidence: 99%